Deformation of Special Relativity in Ultra-High Energy Astrophysics - Ter-Kazarian, G.
We review deformation of both postulates of Special Relativity (SR) theory, tested in experiments for ultra-high energy cosmic ray (UHECRs) and TeV-γ photons observed. To this aim, we utilize the theory of, so-called, master space (MSp) induced supersymmetry (Ter-Kazarian, 2023, 2024), wherein the standard Lorentz code (SLC) is derived in a new perspective of double global MSp-SUSY transformations in terms of Lorentz spinors (θ, ¯θ) referred to MSp. This allows to introduce the physical finite relative time interval between two events as integer number of the own atomic duration time of double transition of a particle from M4 to MSp and back. While all the particles are living on M4, their superpartners can be viewed as living on MSp. This is a main ground for introducing MSp, which is unmanifested individual companion to the particle of interest. Continuing along this line, in present communication we address the deformation of these spinors: θ → ˜θ = λ1/2 θ, etc., where λ appears as a scalar deformation function of the Lorentz invariance (LIDF). This yields both the DLE and DMAV, respectively, in the form ˜ ds = λds and ˜c = λc, provided, the invariance of DLE, and the same value of DMAV in free space hold for all inertial systems. Thus, the LID-generalization of global MSp-SUSY theory formulates the generalized relativity postulates in a way that preserve the relativity of inertial frames, in spite of the appearance of modified terms in the LID dispersion relations. We complement this conceptual investigation with testing of various LIDFs in the UHECR- and TeV-γ threshold anomalies by implications for several scenarios: the Coleman and Glashow-type perturbative extension of SLC, the LID extension of standard model, the LID in quantum gravity motivated space-time models, the LID in loop quantum gravity models, and the LIDF for the models preserving the relativity of inertial frames.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture